DAMPAK PERSEPSI HARGA, CITRA MEREK DAN SERTIFIKASI HALAL DALAM MENCIPTAKAN KEPUTUSAN PEMBELIAN INDOMIE - Wahyuningsih, Sri; Octavia, Ayu Nurafni (JURNAL PUNDI, 2025)
The aim of this research is to analyze the influence of price perception, brand image and halal certificate on the purchase decision Indomie brand instant noodles at the Warmindo “Purie” stall in Grobogan Regency. The population of this research is consumers who buy Indomie brand instant noodles at the Warmindo Purie stall, Jl. Pilang Kidul, Gubug District, Grobogan Regency whose numbers and numbers cannot be predicted. The sample taken was 96 consumers. The type of data used is primary data. The data collection method uses a questionnaire. Meanwhile, the analysis technique used is multiple regression analysis by carrying out the t-test and coefficient of determination. The results of the analysis show that: Price perception is proven to have a positive and significant effect on purchase decision. Brand image is proven to have a positive and significant effect on purchase decisions. Halal certificates have been proven to have a positive and significant effect on purchase decisions